Sources of Information on National Issues among Border Communities in Yobe State, Nigeria - Idris, Mohammed Khalid; Msughter, Aondover Eric (ASEAN Journal of Community Engagement, 2022)
Information has been termed as power in the 21st century. Every century has its uniqueness, and the uniqueness of the 21st century is the availability, ease of access, proliferation, and strength of information. This study examines the sources of information among border communities in Yobe State. The study attempts to find out how people in border communities in Yobe State access information and the specific sources of information they have access to, including non-mass mediated channels and platforms.It also strives to ascertain if people in border communities in Yobe State get information on national issues and, if so, how frequently do they get information on national issues,as well as the level of influence of international broadcast organizations on the perceptions of people in border communities in Yobe State. The study adopts source credibility and source complementarity theories and employs multiple-stage sampling,in which cluster sampling, raffle method of simple random sampling, and convenient sampling were used. Based on the findings, many of the respondents in the selected local governments stated that they accessed information through mediums like radios, televisions, computers, or mobile devices but did not have access to information in their respective communities. The data shows that 48.6% of the respondents in the selected local governments in Yobe State have access to specific media through which they get information. Further, the findings show that Sahel FM is a major source of information in the state as attested by 55.7% of the respondents. The study concludes that there is a need for people in the state to have substantial access to information through local media on issues affecting them in the rural areas rather than depending on foreign stations for information.